Respuesta :
(f+g)(x) = f(x) + g(x)
(f+g)(x) = 3x-2 + 2x+1
(f+g)(x) = (3x+2x) + (-2+1)
(f+g)(x) = 5x - 1
(f+g)(x) = 3x-2 + 2x+1
(f+g)(x) = (3x+2x) + (-2+1)
(f+g)(x) = 5x - 1
Answer:
5x-2
Step-by-step explanation:
If f(x) = 3x – 2 and g(x) = 2x + 1
we need to find (f + g)(x)
[tex](f + g)(x)= f(x) + g(x)[/tex]
Replace f(x) and g(x) in the given equation
[tex](f + g)(x)= f(x) + g(x)=3x-3+2x+1[/tex]
Now we combine like terms
[tex](f + g)(x)= f(x) + g(x)=3x-3+2x+1=5x-2[/tex]
[tex](f + g)(x)=5x-2[/tex]